Handoff communication in intensive care: links with patient safety - Grazielle Rezende da Silva dos Santos; Juliana Faria Campos; Rafael Celestino da Silva (Universidade Federal do Rio de Janeiro, 2018)
Abstract Objective: To gather scientific evidence about ICU handoff practices and their implications on the safety of communication among team members about hospitalized patients. Method: This was an integrative review conducted in the Medline, PubMed, Cinahl and Scopus databases with the descriptors patient handoff, communication, patient safety, critical care, health communication and intensive care unit. The adopted criteria were: full text, in Portuguese or English, in the last 10 years, with level of evidence over IV and compliance to the study question. Fifteen articles were submitted to a structured tool and analysis. Results: There is evidence of incompleteness, absence or errors in handoff information, caused by the lack of standardization and preparation for this activity, generating delayed, incorrect or non-performed procedures. The use of tools reduces the amount of omitted information, side talks, and errors, improving team satisfaction. Final considerations: It is necessary to promote safe communication in handoff, implementing practices that ensure care continuity.